The usage of social media: visibility elements and business growth among entrepreneurs’ society in Terengganu / Khalid Amin Mat ... [et al.] - Mat, Khalid Amin; Omar Ali, Siti Rapidah; Mohd Said, Nur Shafini; Abdullah, Nasiha; Husain, Muhammad Hafiz (Universiti Teknologi MARA, Perlis, 2021)
The study aims to analyse the relationship between visibility elements using social media that contribute most to business growth among Entrepreneurs Society in Terengganu. A questionnaire consisting of seven sections (A-G) was distributed to collect the needed information: Section A, the respondents’ demographic background; Section B, the construction of business page; section C, the establishment of the community; section D, content information management; section E, analysing customer behaviour is studied; section F, market optimization opportunities; and section G, business growth. The population for this research is 87 entrepreneurs from the Entrepreneurs Society in Terengganu and from that amount 76 respondents had successfully participated. The Statistical Package for the Social Science version 25 is used to examine the result of this study. Research has revealed that the established reliability of the measurement is very strong. Cronbach Alpha is a coefficient correlation that indicates how well all the items of the average in a set of positive correlation to one another. The result of the reliability of analysis for business growth shows that Cronbach Alpha are the right tools to use. The mean of value for all variables is strong. The Pearson correlation for the relationship of business growth with the construction of the business page, the establishment of community, content information management, and analysing customer behaviour is a positive relationship with a significant value of P<0.05. In conclusion, from hypothesis one until hypothesis four, the construction of the business page, the establishment of community, content management information, and analysing customer behaviour have a significant relationship with business growth. Researchers found out that four hypotheses are accepted, and one is rejected which is the measurement of business growth. Lastly, the researchers are hoping that all entrepreneurs and business organizations can gain benefit from this study.